Studi Pembuatan Minuman Serbuk Ekstrak Mawar Merah dengan Metode Foam Mat Drying - Rahmawati, Nisa; Saati, Elfi Anis; Wachid, Mochammad (Food Technology and Halal Science Journal, 2020)
Foam mat drying is a drying method that produced powder with better quality compared to conventional drying. The research aimed to analyze the effect of egg albumen concentration as a foaming agent and the addition of different types of sugar on red rose instant powder properties. Nested design by two factors with 3 replications was applied in this research. The first was concentration of egg albumen as the nest with 3 levels (6%, 8%, and 10%) and the second was the addition type of sugar as the nested part with 3 types (granulated sugar, corn sugar, and palm sugar). The results showed that the effect of concentration egg albumen significant (p< 0.05) on the water content, pH, total dissolved solids, anthocyanin levels, antioxidant activity, color intensity (L and a+) and appearance. The different types of sugar addition gave a significant effect (p<0.05) on water content, total dissolved solids, appearance, aroma, and taste. Water content and an ash content of red rose instant powder has been according to the Indonesian National Standard (SNI 01-4320-1996) instant powder drink. The best treatment proved by the concentration of 6% egg albumen and the addition of corn sugar with the value of moisture content of 2.46 %, an ash content of 0.42 %, solubility 86.47 %, water absorption 35.44 %, pH 4.11, total dissolved solid 10.2 ˚Brix, anthocyanin level 77.24 mg/L, antioxidant activity 69.82%, color intensity (L: 49.8 and a +: 36.4) and hedonic tests (appearance, aroma, and taste) of red rose instant powder were accepted by panelist.